2021
DOI: 10.1039/d1tc01557e
|View full text |Cite
|
Sign up to set email alerts
|

Combining 3D printing and screen-printing in miniaturized, disposable sensors with carbon paste electrodes

Abstract: In this paper we report on a modular design that allows one to fabricate electrochemical sensors upon combining 3D printing and screen printing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The speed at which additive manufacturing produces goods, especially in large quantities, prevents it from being used profitably. As a result, hybrid procedures are concluded by contemporary research, which include the integration of additive processes into the regular industrial production process [ 93 , 94 , 95 ]. Additive manufacturing requires a repeatable process due to its sequential nature.…”
Section: Embedded Sensors With 3d Printing Technologymentioning
confidence: 99%
“…The speed at which additive manufacturing produces goods, especially in large quantities, prevents it from being used profitably. As a result, hybrid procedures are concluded by contemporary research, which include the integration of additive processes into the regular industrial production process [ 93 , 94 , 95 ]. Additive manufacturing requires a repeatable process due to its sequential nature.…”
Section: Embedded Sensors With 3d Printing Technologymentioning
confidence: 99%
“…Sensors are also used in the design of intelligent packaging, some of which can be obtained by 3D printing [164,216]. To this end, nanomaterial-based functional ink formulations with innovative electronic designs and architectures printed on packaging materials are used to achieve various functionalities, such as radio frequency communication, timetemperature indicators, gas sensors, and freshness indicators, among others.…”
Section: Intelligent and Smart Food Packagingmentioning
confidence: 99%
“…28 3D printing combined with screen-printing was demonstrated by Materon et al to help increase the sensor surface area and improve the sensitivity towards specific analytes. 29 Additionally, Kerr et al also investigated numerous SPEs from Zensor, DropSens, and Kanichi, where they noticed platinum and gold SPEs produced low electrogenerated chemiluminescence, while carbon SPEs produced better signals. 30 In this study, they concluded that nanomaterial modification did not enhance the electrogenerated chemiluminescence, although previously mentioned modifications demonstrated that surface area seemed to be the critical z E-mail: zhe.she@queensu.ca component to improve the overall sensor performance for sensing applications.…”
mentioning
confidence: 99%